Analisis Preferensi Pengunjung dan Positioning Pusat Perbelanjaan Modern di Kota Bogor (Studi Kasus: Botani Square, Ekalokasari Plaza, Bogor Trade Mall, dan Pangrango Plaza) - Munandar, Jono M.; Hermawan, Y.E. (Jurnal Manajemen, 2009)
The glowing of modern shopping center (MSC) development in Bogor City has caused competition between the promoters of MSC to seized on visitor’s heart.  It needs more attention of the MSC’s promoters to know about the visitor behavior. The purpose of this research is: (1) to identify the step of MSC’s visitor decision making in Bogor City, (2) to know about the preference of visitor for the attribute of MSC in Bogor City, (3) to know about the positioning of MSC in Bogor City, for the case study in Botani Square, Ekalokasari Plaza, Bogor Trade Mall and Pangrango Plaza. The data used in this research was in form of primary and secondary data. Data was analyzed by using descriptive analysis, importance performance analysis (IPA), and multidimensional scaling (MDS). The result of the data processing by using multidimensional scaling showed that each of MSC has each characteristic for position in perceptual map.  Furthermore, it was found in the perceptual map that there are three MSC which have close position each other; they are Botani Square, Ekalokasari Plaza, and Pangrango Plaza. That close position showed that Botani Square is the direct competitor of Ekalokasari Plaza and Pangrango Plaza. That perceptual map also showed that Ekalokasari Plaza has the best positioning strategy, because it has the most dominant nearness with two dimensions; namely: 1) supporting facility dimension and 2) completeness of tenant variation dimension.Kata kunci: Modern Shopping Center, Visitor Decision, Preferences, Positioning.